2005
DOI: 10.1152/ajpheart.01039.2004
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase inhibitor PJ-34 reduces mesenteric vascular injury induced by experimental cardiopulmonary bypass with cardiac arrest

Abstract: -The aim of this study was to investigate effects of poly(ADP-ribose) polymerase (PARP) inhibition on mesenteric vascular function and metabolism in an experimental model of cardiopulmonary bypass (CPB) with cardiac arrest. Twelve anesthetized dogs underwent 90-min hypothermic CPB. After 60 min of cardiac arrest, reperfusion was started for 40 min following application of either saline vehicle (control, n ϭ 6) or a potent PARP inhibitor, PJ-34 (10 mg/kg iv bolus and 0.5 mg ⅐ kg Ϫ1 ⅐ min Ϫ1 infusion for 20 min,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…Mounting evidence has suggested that NAD and NADP metabolism also plays significant roles in vascular damage under various pathological conditions. For example, a PARP inhibitor was found to decrease cardiopulmonary bypass-induced mesenteric vascular dysfunction by improving hemodynamics, decreasing neutrophil adhesion, and restoring nitric oxide production (12); and the C242T CYBA polymorphism of NADPH oxidase was found to be associated with essential hypertension (205).…”
Section: G Nad and Nadp In Vascular Activitymentioning
confidence: 99%
“…Mounting evidence has suggested that NAD and NADP metabolism also plays significant roles in vascular damage under various pathological conditions. For example, a PARP inhibitor was found to decrease cardiopulmonary bypass-induced mesenteric vascular dysfunction by improving hemodynamics, decreasing neutrophil adhesion, and restoring nitric oxide production (12); and the C242T CYBA polymorphism of NADPH oxidase was found to be associated with essential hypertension (205).…”
Section: G Nad and Nadp In Vascular Activitymentioning
confidence: 99%
“…They concluded that cardiac preservation (global deep hypothermic ischemia) followed by reperfusion leads to a significant activation of PARP, which was blocked by the novel PARP inhibitor PJ34 [108]. In a dog model, pharmacological PARP inhibition with PJ34 during reperfusion represents a viable modality to achieve not only better heart function [108,109] but also intestinal protection against the cardiopulmonary bypass associated malperfusion damage [110]. PJ34 significantly attenuated the CHF-induced suppression of systolic +dP/dt and diastolic dP/dt and an increase in left ventricular end diastolic pressure (LVEDP); it also improved decreased mean blood pressure in CHF and also tended to increase left ventricular systolic pressure (LVSP) [111].…”
Section: Insulin Inhibits Apoptosis At Early Reperfusion and Reduces mentioning
confidence: 99%
“…It is classified as a phenanthridinone and besides its PARP-inhibiting activity it exhibits also antiviral and anti-tumorous functions (Lin et al, 2014 ; Liang et al, 2015 ). Additionally, Szabo et al ( 2004a , b ) and Andrasi et al ( 2005 ), demonstrated in a canine model of CPB that administration of PJ34 was able to significantly reduce endothelial dysfunction of mesenteric vessels (frequently seen after CPB). Moreover, it improved myocardial contraction and even pulmonary function.…”
Section: Introductionmentioning
confidence: 99%